2013
DOI: 10.1111/cns.12210
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms Underlying the Long Duration of Action of Thienorphine, A Novel Partial Opioid Agonist for the Treatment of Addiction

Abstract: These results indicate that multiple factors, including persistent receptor occupation and enhanced receptor downregulation, may contribute to the long-lasting effects of thienorphine that would be beneficial for its application in addiction treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The primary mechanisms underlying the inhibitory effect of agmatine on opioid use disorder and relapse involve ① the acceleration of opioid-induced μ receptor trafficking, recycling and resensitization, ② a reduction in dopamine release via enhancement of negative feedback modulation by dynorphinand ③ modulation of glutamate neurotransmissions. DA, dopamine; GRK, GPCR kinases long-lasting effects of thienorphine (Yu et al, 2014). Given that the abused opioid is unable to activate enough μ receptor to produce an abuse-related effect when a sufficient number (>80%) of μ receptor are occupied (Greenwald et al, 2014), thienorphine-induced decrease in unoccupied μ receptor reserves would be beneficial for its application as a candidate therapeutic for opioid use disorder.…”
Section: The Opioid Receptor Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary mechanisms underlying the inhibitory effect of agmatine on opioid use disorder and relapse involve ① the acceleration of opioid-induced μ receptor trafficking, recycling and resensitization, ② a reduction in dopamine release via enhancement of negative feedback modulation by dynorphinand ③ modulation of glutamate neurotransmissions. DA, dopamine; GRK, GPCR kinases long-lasting effects of thienorphine (Yu et al, 2014). Given that the abused opioid is unable to activate enough μ receptor to produce an abuse-related effect when a sufficient number (>80%) of μ receptor are occupied (Greenwald et al, 2014), thienorphine-induced decrease in unoccupied μ receptor reserves would be beneficial for its application as a candidate therapeutic for opioid use disorder.…”
Section: The Opioid Receptor Systemmentioning
confidence: 99%
“…Thienorphine, a chemically new opioid and buprenorphine analogue, was developed at our institute. Competitive receptor binding and [ 35 S]GTPγS binding assays have shown that thienorphine is a potent non‐selective partial agonist at μ and κ receptors (J. X. Li et al, 2007; Yu, Li, et al, 2014; Yu, Yue, et al, 2006). Compared with buprenorphine, thienorphine exhibits higher binding affinity for μ receptor, higher antinociceptive and a longer duration of action (long‐lasting effects), along with better oral bioavailability (Yu, Li, et al, 2014; Yu, Yue, et al, 2006).…”
Section: Potential Targets or Treatment Strategies For Opioid Use Dis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Thienorphine (TNP), N-Cyclopropylmehtyl-7α-[(R)-1-hydroxyl-1-methyl-3-(thien-2-yl)propyl]-6, 14-endoethanotetrahydronooripavine, was synthesized as a ramification of buprenorphine, and identified to be a novel non-selective opioid partial agonist (Liu et al, 2005 ; Yu et al, 2006 ). When compared with buprenorphine, TNP showed high binding affinity with the μ-opioid receptor in vitro and a better oral bioavailability in vivo (Li et al, 2007 ; Yu et al, 2013 ). TNP was developed for the treatment of opioid dependence.…”
Section: Introductionmentioning
confidence: 99%